Human impact since medieval times in the western part of Lublin Polesie against the background of Holocene climate changes: record from Lake Mytycze in the Wieprz-Krzna Canal System (SE Poland). (10th March 2021) - Jarosz, J.; Pidek, I.A.; Urban, D.; Lamentowicz, M.; Michczyński, A.
Abstract: The main objective of the study was to reconstruct palaeoenvironmental changes recorded in lake and peatland sediments from the peatland located in the western part of Lublin Polesie, where no former palaeoecological research had been conducted, and to compare findings to changes reconstructed for other sites in the eastern part of this region. Climate changes were considered, as well as the effects of human impact, which intensified particularly after the Middle Ages. In recent times the trajectory of change of the Mytycze ecosystem was exceptional because in the 1960s this area was included in the Wieprz-Krzna Canal System, and then renaturated after the discontinued use of hydraulic engineering structures. This is the largest canal in Poland and runs in the immediate vicinity of the watershed supplied by two large rivers: the Bug and the Wieprz. The presented study mainly relied on the following proxies: pollen, testate amoebae and other non-pollen palynomorphs, and peat decomposition. Data from the Archaeological Picture of Poland (AZP) allowed for a detailed reconstruction of chronological changes in the palaeoenvironment. An important aspect of this study was also the first ever use of testate amoebae remains in the reconstruction of the Lublin Polesie environment. Findings from research on the Mytycze site for the first time confirmed that the beginning of the formation of the lake basin was similar to that reconstructed for all other lakes in the Lublin Polesie region investigated previously with multidisciplinary methods, and dates to the end of the late glacial of the Vistulian. The early phase of the peatland formation resulting from the shallowing of the lake was very long and lasted from the Subboreal period to the 15th century. The youngest phases with records of human impact are characterised by increased human pressure (intensified cultivation of cereals, buckwheat, legumes and brassica crops) after the Wieprz-Krzna Canal System was put into use, and intensified grazing in the vicinity of Lake Mytycze. This phase, dated to the 1970s, is followed by a marked increase in the water level, which was probably related to the supply of water to the dammed Lake Mytycze from Wieprz-Krzna Canal via Lake Dratów. Records in the upper part of the core indicate the return of Sphagnum spp., most likely due to the cessation of the use of hydraulic engineering structures and the renaturation of the lake and peatland ecosystem, which led to the appearance of valuable species of plants and birds.